2017
DOI: 10.1007/s11571-017-9459-8
|View full text |Cite
|
Sign up to set email alerts
|

Measures of entropy and complexity in altered states of consciousness

Abstract: Quantification of complexity in neurophysiological signals has been studied using different methods, especially those from information or dynamical system theory. These studies have revealed a dependence on different states of consciousness, and in particular that wakefulness is characterized by a greater complexity of brain signals, perhaps due to the necessity for the brain to handle varied sensorimotor information. Thus, these frameworks are very useful in attempts to quantify cognitive states. We set out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 41 publications
8
93
0
Order By: Relevance
“…This regularity gives less number of different permutation vectors and this provokes a decrease in the entropy and complexity values. Similar result where shown comparing awake people with people in altered state of consciousness such as sleep, seizure and coma, [11]. Analogous results are shown in other epilepsy syndromes such as absence crises, [12].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…This regularity gives less number of different permutation vectors and this provokes a decrease in the entropy and complexity values. Similar result where shown comparing awake people with people in altered state of consciousness such as sleep, seizure and coma, [11]. Analogous results are shown in other epilepsy syndromes such as absence crises, [12].…”
Section: Discussionsupporting
confidence: 74%
“…Note that in this work low values in the plane correspond to pathological clinical conditions or changes in the state of consciousness. [11,12]. For example, as shown in the first case, the low values correspond to changes found in the signal given by patterns (graphs) of pathological discharges in intercritic studies of a patient with epilepsy.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Effects of these input parameters should also be confirmed and correlated with FFT based methods to characterise how these input parameters might limit the analyses for some frequency ranges [44] in sleep research. Validation of PLZC analysis should also be performed on larger datasets to confirm the usefulness of this method even though previous studies reported consistent findings of complexity in altered consciousness (i.e., higher complexity in wakefulness [70] and REM sleep compared to NREM) in EEG durations as short as two to four minutes [71].…”
Section: Discussionmentioning
confidence: 95%